2020
DOI: 10.1021/acs.macromol.0c01886
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Protein-Inspired Synthetic Random Heteropolymers

Abstract: Random heteropolymers (RHPs) are an interesting class of materials useful in many theories and applications. While previous studies typically focused on simplified RHP systems, here we explore a more complex scenario inspired by highly heterogeneous molecules like proteins. Our system consists of four monomers mimicking different classes of amino acids. Using Molecular Dynamics simulations and Small-Angle X-Ray Scattering, we explore dynamical and structural features of these RHPs in solution.Our results show … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 87 publications
4
44
0
Order By: Relevance
“… 25 27 Kratky plots of each PBP revealed bell-shaped curves with a clear local maximum, suggesting that each brush polymer has a compact structure generated by folded chains ( Figure S14c ). 25 , 28 This conclusion was further supported by calculating the Stokes ratio, ρ = R g / R h , for each PBP ( Table S2 ). Generally, for the PBPs, ρ was approximately 0.776, consistent with the expected behavior for spherical particles, including globular proteins.…”
Section: Resultsmentioning
confidence: 64%
“… 25 27 Kratky plots of each PBP revealed bell-shaped curves with a clear local maximum, suggesting that each brush polymer has a compact structure generated by folded chains ( Figure S14c ). 25 , 28 This conclusion was further supported by calculating the Stokes ratio, ρ = R g / R h , for each PBP ( Table S2 ). Generally, for the PBPs, ρ was approximately 0.776, consistent with the expected behavior for spherical particles, including globular proteins.…”
Section: Resultsmentioning
confidence: 64%
“…Herein, we explore RHP behavior using unbiased atomistic molecular dynamic methods with the Amber MD package, similar to our prior work. 10,26 Through a series of successive anneal cycles to 500 K in implicit water, ten conformations each of two distinct polymer sequences were created and then annealed to 650 K in explicit solvent: water, DMSO, THF, or hexane. The resulting single chain conformations at 300 K from these simulations were used for analysis.…”
Section: Lettermentioning
confidence: 99%
“…The two random heteropolymer sequences investigated, Sequence 1 and Sequence 2 as shown in Figure 1, are composed of the methacrylate-based building blocks studied previously. 10 Sequence 1 contains all four monomer species-methyl methacrylate (MMA), oligo(ethylene glycol)methacrylate (OEGMA), 2-ethylhexyl methacrylate (EHMA), and 3-sulfopropyl methacrylate (SPMA)-used in the prior work, while Sequence 2 is similar but lacks the anionic SPMA monomer. Both sequences formed compact globular structures in water and hexane, with distinct surface compositions in each solvent apparent by visual inspection in Figure 1.…”
Section: Lettermentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that synthetic random heteropolymers with statistically controlled side chain compositions are able to exhibit protein-like functions even without the peptide backbone. [6][7][8][9] To this end, synthetic polypeptides prepared by the ring-opening polymerization (ROP) of N-carboxyanhydrides (NCA) have emerged as promising protein mimics with the potential to synergize the advantages of both peptides and synthetic polymers. [10][11][12][13][14][15] Specifically, polypeptides possess the same backbone and secondary conformations as protein and can be efficiently produced at up to kilogram scales and a high number-averaged molecular weight (Mn).…”
Section: Introductionmentioning
confidence: 99%